Pengeringan Padi (Oryza sativa L) pada Musim Hujan - Sinaga, Elisabeth Intan; Tamrin, Tamrin; Asmara, Sandi; Kuncoro, Sapto (abe.fp.unila.ac.id, 2023)
Indonesia is one of the countries where the majority of the population are farmers, and rice is the main commodity. While rice drying is an important factor, the current climate and weather changes are an obstacle for farmers in the drying process. Rice with high moisture content is not safe for storage as it is susceptible to mold attack and deterioration. The purpose of this research was to study the effect of the level of inclination of the plastic position on the decrease in rice moisture content and the level of loss. The results of observations of the weather index for 4 days show that the intensity of the sun reaching the earth varies every hour. The parameters measured rice weights of 250 grams, 500 grams, and 750 grams showed that at a slope of 30 ° had the lowest moisture content and the highest rate of rice loss was in rice weights of 250 grams with a slope of 0 ° at 62% while the lowest rate of rice loss was in rice weights of 750 grams with a slope of 0 ° at 19%. Keywords: Rice, Drying, Moisture Content Rice Weight, Slope.